HMGCS2 is a key ketogenic enzyme potentially involved in type 1 diabetes with high cardiovascular risk - Shukla, Sanket Kumar; Liu, Weijing; Sikder, Kunal; Addya, Sankar; Sarkar, Amrita; Wei, Yidong; Rafiq, Khadija (Scientific reports, 2017)
Diabetes increases the risk of Cardio-vascular disease (CVD). CVD is more prevalent in type 2 diabetes (T2D) than type 1 diabetes (T1D), but the mortality risk is higher in T1D than in T2D. The pathophysiology of CVD in T1D is poorly defined. To learn more about biological pathways that are potentially involved in T1D with cardiac dysfunction, we sought to identify differentially expressed genes in the T1D heart. Our study used T1D mice with severe hyperglycemia along with significant deficits in echocardiographic measurements. Microarray analysis of heart tissue RNA revealed that the T1D mice differentially expressed 10 genes compared to control. Using Ingenuity Pathway Analysis (IPA), we showed that these genes were significantly involved in ketogenesis, cardiovascular disease, apoptosis and other toxicology functions. Of these 10 genes, the 3-Hydroxy-3-Methylglutaryl-CoA Synthase 2 ( HMGCS2 ) was the highest upregulated gene in T1D heart. IPA analysis showed that HMGCS2 was center to many biological networks and pathways. Our data also suggested that apart from heart, the expression of HMGCS2 was also different in kidney and spleen between control and STZ treated mice. In conclusion, The HMGCS2 molecule may potentially be involved in T1D induced cardiac dysfunction.